Cytokines in autoimmunity. - Brennan, F; Feldmann, M (1992)
It is now generally accepted that many cytokines are involved in the pathogenesis of autoimmune disease, either directly by causing tissue destruction or indirectly through the activation of autoreactive and inflammatory cells. Thus, cytokines, such as tumor necrosis factor-alpha, are implicated in the pathogenesis of rheumatoid arthritis based on in vitro studies on synovial tissue from patients with rheumatoid arthritis, which suggest that the effects of tumor necrosis factor-alpha are amplified by its potential to induce other pro-inflammatory cytokines, such as interleukin-1 and granulocyte-macrophage colony-stimulating factor. Transgenic mouse technology has shown that mice expressing the human tumor necrosis factor-alpha gene develop a polyarthritis. Interleukin-2 has also been identified by transgenic technology as a cytokine involved in the pathogenesis of insulin-dependent diabetes mellitus through the activation and stimulation of growth of autoreactive T cells.